“Paste test” – a method for evaluating the fungal inhibition potential of ground wood samples - Keržič, Eli (Acta silvae et ligni, 2025)
As part of the »ULTRA – University of Ljubljana for a Sustainable Society« project, a new test method was introduced into the curriculum to provide insight into key properties that affect wood durability. This study aimed to adapt and verify the “paste test”, which uses wood dust in nutrient media to assess the inhibitory effect of wood components on fungal growth. The method was adapted to match the available laboratory equipment and simplified for educational use by students at the Department of Wood Science and Technology (Biotechnical Faculty, University of Ljubljana, Slovenia). The study involved testing fungal growth on nutrient media supplemented with spruce wood dust, with the goal of evaluating different grinding methods, nutrient media, and data analysis. Potato dextrose agar nutrient media was confirmed as a suitable alternative to malt extract agar. The wood dust fraction size had no significant effect on fungal inhibition, enabling the use of coarser, less time-saving grinding methods. Image analysis and logistic growth modelling were conducted using freely available software (ImageJ and R-Commander), which proved to be effective alternatives to proprietary tools. Visualization of growth using logistic growth rates offered a clearer comparative analysis, despite some loss of dynamic growth information.
Keywords: brown rot fungi; glive bele trohnobe; glive rjave trohnobe; hranilno gojišče; inhibicija; inhibition; kemija lesa; logistic growth rate; logistična stopnja rasti; nutrient media; white rot fungi; wood chemistry